Antisense oligonucleotides: the promise and the problems - Frazier, Kendall S. (Henry Stewart Talks, 2015)
Antisense oligonucleotide (ASOs) therapies, Screening strategies for drug candidates, Locked nucleic acid (LNA) gapmers, Understanding off-target effects (OTEs), Mechanisms of ASO toxicity and clinical relevance, New targets/delivery systems under development